A rare gas-containing lumbar synovial cyst treated by percutaneous transforaminal endoscopic cystectomy: A case report and literature review - Wei, Ziran; Lin, Qian; Zhang, Hao; Zhang, Haoyun; Ma, Xuexiao; Wang, Chao (Frontiers in Surgery, 2023)
Spinal synovial cysts are rare entities for which standard surgical strategies are inconsistent. Here, we present an uncommon intraspinal gas-containing synovial cyst treated by percutaneous transforaminal endoscopic cystectomy. A 52-year-old man presented with radicular pain and intermittent claudication that had persisted for one month. Computed tomography revealed an intraspinal cystic lesion anteromedial to the left L4/5 articular joint and the center of the lesion manifested gas contents. A transforaminal endoscopic procedure was performed and confirmed as a safe and minimally invasive technique for gas-containing lumbar synovial cysts. It provides a valuable substitution and supplementation to open surgery.